Randomized clinical trial assessing anti-gingivitis efficacy of two stannous fluoride dentifrices and zinc/arginine dentifrice - He, Tao; Mazor, Sigal; Zou, Yuanshu; Grender, Julie; Farrell, Svetlana; Sagel, Paul; Biesbrock, Aaron R; Timm, Hans; Zini, Avi (American journal of dentistry, 2021)
To evaluate the anti-gingivitis efficacy of two bioavailable stannous fluoride (SnF2) dentifrices versus a zinc/arginine dentifrice and a negative control dentifrice, and to compare the plaque control benefits. This was a single-center, randomized, controlled, four-treatment, parallel-group, double-blind, 3-month clinical trial. Healthy adult subjects with gingivitis were randomly assigned to one of four different dentifrice treatment groups: SnF2 dentifrice A, SnF2 (1,100 ppm F) + sodium fluoride (350 ppm F) + sodium hexametaphosphate (Procter & Gamble); SnF2 dentifrice B, SnF2 (1,100 ppm F) + sodium fluoride (350 ppm F) + citrate (Procter & Gamble); Zn/Arg dentifrice, zinc/arginine + sodium fluoride (1,450 ppm F) (Colgate-Palmolive); negative control dentifrice, sodium monofluoro-phosphate (1,000 ppm F) + sodium fluoride (450 ppm F) (Colgate-Palmolive). Subjects brushed with their assigned treatment dentifrice and an assigned manual toothbrush (Oral-B Indicator) for 1 minute, twice daily, for the duration of the study. Gingivitis was assessed at Baseline and at Weeks 2, 4 and 12 by calculating the total number of gingival bleeding sites using the Gingival Bleeding Index, and plaque was assessed at Baseline and at Week 12 using the Turesky Modified Quigley-Hein Index. A repeated measures model was carried out across Weeks 2, 4, and 12 to determine bleeding efficacy (total number of bleeding sites). An ANCOVA with baseline plaque as the covariate was used to evaluate plaque efficacy at Week 12. 161 subjects were randomized (mean age= 38.8 years). 154 subjects completed the study and 153 had evaluable data at Week 12. The mean (SD) number of Baseline bleeding sites overall was 78.74 (31.16) with no significant difference between groups (P= 0.537). SnF2 dentifrice A significantly reduced the number of bleeding sites relative to the negative control dentifrice at Weeks 2, 4 and 12 by 15.4%, 13.7% and 17.2%, respectively. SnF2 dentifrice B significantly reduced the number of bleeding sites relative to the negative control dentifrice at Week 4 by 13.9% (P= 0.041). Relative to the Zn/Arg dentifrice, SnF2 dentifrice A produced significantly greater reductions in gingival bleeding sites at Weeks 2, 4 and 12 by 23.4%, 17.2% and 20.9%, respectively (P≤ 0.007). SnF2 dentifrice B produced significantly greater bleeding reductions versus the Zn/Arg dentifrice at Weeks 4 and 12 by 17.4% and 14.4%, respectively (P≤ 0.035). The Zn/Arg dentifrice did not differ significantly in the number of bleeding sites (P≥ 0.127) or plaque (P= 0.175) relative to the negative control dentifrice. Both SnF2 dentifrices significantly reduced plaque levels (P≤ 0.029) relative to both negative control dentifrice and Zn/Arg dentifrice at Week 12. All dentifrices were well tolerated. Two different SnF2 dentifrices showed significantly reduced gingival bleeding and plaque levels relative to a Zn/arginine dentifrice.